EVALUASI E-BUDGETING DI PEMERINTAH KOTA SURAKARTA (TAHUN ANGGARAN 2018) - ., Wahyuningsih; Harsasto, Priyatno (Journal of Politic and Government Studies, 2020)
The Surakarta City Government implements E-Budgeting through the application ofSIMDA Keuangan. In addition, the Surakarta City Government also implemented a websiteservice for budget transparency. The results in good financial management are indicated bythe approval of Wajar Tanpa Pengecualian status from Badan Pemeriksa Keuangan. Thisstudy aims to evaluate the implementation of E-Budgeting through the role of thebureaucracy in the Surakarta City Government and the social capital involved in budgetallocation decisions making.The research method used is descriptive qualitative research method with datacollection techniques through interviews, observation and literature study. Informants in thisstudy invited seven people from representatives of Bapppeda, BPPKAD, Diskomifo SP andPattiro Surakarta.The results of this study is the implementation of E-Budgeting using the SIMDAKeuangan as a tool to assist regional financial management has been able to facilitate thestages of budgeting, administration, accounting, reporting and accountability in an integratedand accountable. Budget transparency website services need to be maintained periodically tosupport transparency. The relationship between the role of the bureaucracy in theimplementation of E-Budgeting through the Compliance of the Surakarta City Governmentinvolves local financial management regulations. However, there are currently no specificregulations regarding E-Budgeting. The Surakarta City Government is still in theimplementation of E-Budgeting, while the development of the Perwali or Juknis onE-Budgeting is a target for the Surakarta City Government Bureaucracy Reform in 2019-2021. Social capital that is intertwined in the form of linking through the involvement ofelements of society, sectoral communities and other stakeholders is involved in developmentplanning and budget allocation decisions making.Suggestion in this research is the need to improve coordination and quality of humanresources while overseeing the development of Perwali or Juknis for implementingE-Budgeting to support the successful implementation of E-Budgeting in the Surakarta CityGovernment. In addition, the maintenance of a website for budget transparency andsocialization to the public is also needed to increase public involvement in budget oversightin the Surakarta City Government.Keywords: e-budgeting, regional financial management, evaluation process, bureaucracy,social capital.